Abnormal Regional Homogeneity in Patients With Obsessive-Compulsive Disorder and Their Unaffected Siblings: A Resting-State fMRI Study - Yang, Xiangyun; Luo, Jia; Zhong, Zhaoxi; Yang, Xiaojie; Yao, Shumin; Wang, Pengchong; Gao, Jian; Liu, Rui; Sun, Jing; Li, Zhanjiang (Frontiers in Psychiatry, 2019)
Objective: Previous studies suggest that abnormal brain structure and function may be neuroimaging endophenotypes of obsessive-compulsive disorder (OCD). Comparing the intrinsic brain activity of OCD patients and their unaffected siblings will help to further understand the susceptibility to, and pathological mechanisms of, OCD. We used a case control study design aiming to establish whether the abnormal regional homogeneity (ReHo) found in OCD patients also exists in their unaffected siblings. Method: Fifteen unmedicated OCD patients, 15 of their unaffected siblings, and 30 healthy controls (HCs) received resting state functional magnetic resonance imaging (r-s fMRI) scanning and clinical evaluation. We used the ReHo method to analyse the inter-regional synchronised activity of all participants. One-way analysis of covariance with post-hoc tests was used to compare the ReHo maps across groups. A Pearson correlation analysis was conducted to assess the correlations between clinical characteristics and abnormal ReHo in OCD patients. Results: Relative to HCs, OCD patients and their unaffected siblings showed overlapping higher ReHo values in the right dorsolateral prefrontal cortex (DLPFC). Patients with OCD showed increased ReHo in left middle frontal gyrus (MFG) relative to both their unaffected siblings and HCs. In addition to the right DLPFC and left MFG, OCD patients also showed abnormal ReHo in other regions compared to HCs, including higher ReHo in the right superior parietal cortex, and lower ReHo in the left inferior parietal cortex, right parahippocampal region, left thalamus and right inferior temporal cortex. Compared to HCs, the unaffected siblings of patients with OCD had significantly higher ReHo in the right inferior parietal cortex, right MFG and right supplementary motor area. There was no association between clinical symptoms and abnormal ReHo values in OCD patients. Conclusions: This study found overlapping higher ReHo values in the right DLPFC of OCD patients and their unaffected siblings. Our results suggest that the higher ReHo in the right DLPFC may be a potential neuroimaging endophenotype, which may reflect an increased genetic risk of OCD.